Selecting instruments for assessing psychological wellbeing in Afghan and Kurdish refugee groups - Sulaiman-Hill, C.; Thompson, Sandra (BioMed Central Ltd, 2010)
Background. Afghan and Iraqi refugees comprise nearly half of all those currently under United Nations protection. As many of them will eventually be resettled in countries outside the region of origin, their long term health and settlement concerns are of relevance to host societies, and will be a likely focus for future research. Since Australia and New Zealand have both accepted refugees for many years and have dedicated, but different settlement and immigration policies, a study comparing the resettlement of two different refugee groups in these countries was undertaken. The purpose of this article is to describe the instrument selection for this study assessing mental health and psychological well being with Afghan and Kurdish former refugees, in particular to address linguistic considerations and translated instrument availability. A summary of instruments previously used with refugee and migrant groups from the Middle East region is presented to assist other researchers, before describing the three instruments ultimately selected for the quantitative component of our study.Findings. The Kessler-10 Psychological Distress Scale (K10), General Perceived Self-Efficacy Scale (GPSE), and Personal Well-Being Index (PWI) all showed good reliability (Cronbach's alphas of 0.86, 0.89 and 0.83 respectively for combined language versions) and ease of use even for pre-literate participants, with the sample of 193 refugees, although some concepts in the GPSE proved problematic for a small number of respondents. Farsi was the language of choice for the majority of Afghan participants, while most of the Kurds chose to complete English versions in addition to Farsi. No one used Arabic or Turkish translations. Participants settled less than ten years were more likely to complete questionnaires in Farsi. Descriptive summary statistics are presented for each instrument with results split by gender, refugee group and language version completed. Conclusion. This paper discusses instrument selection for Farsi and Arabic speaking refugee participants from the Middle East and Afghanistan, concluding that the Kessler-10, GPSE scale and PWI were suitable for use with these groups. Suitable language translations are freely available. Our experience with these instruments may help inform other studies with these vulnerable groups.